KOMPETENSI PROFESIONAL GURU BAHASA ARAB MADRASAH ALIYAH NEGERI (MAN) DI JAKARTA - Maswani Maswani; Wati Susiawati (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This study aimed to reveal the professional competence of Arabic language teachers of MAN Jakarta, in the aspects of the content of Arabic Skills, as well as their professional competence according to the Principal of MAN, colleagues and the assessment of students. Data collection techniques used were: questionnaire, interview, observation, analysis of content/documents, test, and Focus Group Discussion (FGD). The results showed that the professional competence of the teachers on the mastery of the material were on the category of